Low-Intensity Focused Ultrasound Alleviates Chronic Neuropathic Pain-Induced Allodynia by Inhibiting Neuroplasticity in the Anterior Cingulate Cortex - Wang, Bin (Neural plasticity, 2022)
Copyright © 2022 Bin Wang et al.